Biodiesel Production Using Acid-Base Bi-Functionalized Hydrotalcite Catalyst - Ng, Kai Jun (Universiti Sains Malaysia, 2017)
Due to fossil fuels depletion and its negative impacts towards environment, research on biodiesel production as substitute is gaining more attention. Currently, biodiesel production from non-edible oil is gaining popularity to replace edible oil as feedstocks. However, non-edible oil normally contains high amount of free fatty acid (FFA) and moisture. Thus, acid-base bifunctionalized hydrotalcite (HT) catalyst is choose to study in current paper because simultaneous transesterification and esterification reaction can be carry out without undergoing saponification. HT catalysts were synthesized using combustion method which required much shorter preparation time. Two important parameters to synthesize MgAl based HT i.e. calcination temperature (550oC–750oC) and MgAl ratio (2:1, 3:1) were particularly investigated. The surface morphology, crystallinity, structural and acid strength of the synthesized HT were studied by several characterization techniques. The effect of synthesis parameter on HTs’ characteristics and catalytic performance on biodiesel production were successfully studied. The MgAl based HT catalyst prepared by calcination temperature of 650oC and Mg/Al ratio of 3:1 achieved highest FAME yield (about 68.75%) after 5 hours transesterification reaction using conventional mechanical stirring method from fresh mixed canola-sunflower cooking oil.